Caracterização do perfil dos empreendedores e empreendimentos do centro comercial de Serrinha dos Pintos-RN - Santos, Cosma Daniela dos (Universidade Federal Rural do Semi-Árido, 2018)
Entrepreneurship has been a relevant theme in Brazil and in the world, since this has been the motor that drives economic development and job creation income. In Rio Grande do Norte, it is also very present even in the most inner cities, where the individual entrepreneur microenterprise (MEI) and microenterprise (ME) has been the main source of employment and income. The market has become increasingly dynamic and competitive, and has been progressively demanding innovative products and services. This work aims to analyze and describe the profile of the entrepreneur as well as the ventures in the municipality of Serrinha dos Pintos-RN. To obtain the data collection, a questionnaire was used in which it was possible to obtain an analysis of the quantitative results. The same approach addresses issues that allowed identifying the gender present in the labor market, schooling, and age range of entrepreneurs, time of operation and size of enterprises among other characteristics. According to the survey results it was certified that most entrepreneurs are male, everyone has some kind of education. It was also verified that the commercial branch is predominant in Serrinha dos Pintos-RN. When asked about future claims, the vast majority want to open up making improvements in their business. Finally, I hope that this work will be useful and will serve to correct possible problems encountered in the projects studied and encourage further studies.
Monografia
Keywords: Empreendedorismo; Empreendedor; Comércio; Serrinha dos Pintos-RN; Entrepreneurship; Entrepreneur; Serrinha dos Pintos-RN; Enterprises; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA